Modified Peer Written Corrective Feedback on Dialogue Drafting of Twelfth Graders: Focusing on Linguistic Features - Lasti'ah, Lasti'ah (English Department, Universitas Negeri Surabaya, 2021)
Writing skill is regarded as troublesome for students, leading to errors occurring in the students’ writing. Thus, this paper aims to explore the linguistic feature errors in students' writing and how those errors can be minimized by modified peer-written corrective feedback. This study employed a qualitative method with Classroom Action Research (CAR) design through content analysis. The data was collected from vocational high school students’ composition of the dialogue draft on the ‘offering help’ theme. The results reveal that apart from their level of proficiency, students make errors more on linguistic features in their first phase than in their second phase. It is due to the role of modified peer-written corrective feedback given by their peers of different groups. This feedback assists the students in learning their linguistic aspect errors in their writing. In the process of writing, the modified written corrective feedback is imperative to spur students to apply good linguistic features in their writing. In such a case, learning from peer feedback is a good technique since the process becomes the priority rather than the final product. Finally, modified peer-written corrective feedback is effective in enhancing the students’ writing skills, particularly in writing dialogue.